Mechanisms of a 3-axis CNC machine design and experiment - Youcef Guerfi; Abderrahmane Khechekhouche; Ismail Far; Ishak Kiati; Antar Chekima (ASEAN Journal of Science and Engineering Education, 2021)
CNC technology has become a requirement in the industrial world without complying with educational, pedagogical and private ratings. Manufacturers of this type of machine are trying to conform with the marketing requirements in terms of quality, price and quantity, so the CNC machine can meet the requirements and has acquired a leading position. The study and design of the three-axis CNC machine are based on the Fusion 360 software for the design and PROTEUS software for simulation to perfect our device.